2012
DOI: 10.1111/j.1443-1661.2012.01384.x
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal cutting biopsy technique for histological diagnosis of suspected gastrointestinal stromal tumors of the stomach

Abstract: The mucosal cutting biopsy technique is a useful diagnostic modality for the diagnosis of gastric GIST and for selection of the appropriate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…These new methods include suck-ligate-unroof-biopsy (SLUB) 11, block biopsy via submucosal endoscopy with a mucosal flap method (SEMF) 12 13, mucosal cutting biopsy 14, and endoscopic partial resection with the unroofing technique (EPR-UT) 15. SLUB is a cap-based technique that involves suctioning the tissue into a cap and subsequently tightening a detachable loop to ligate the lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These new methods include suck-ligate-unroof-biopsy (SLUB) 11, block biopsy via submucosal endoscopy with a mucosal flap method (SEMF) 12 13, mucosal cutting biopsy 14, and endoscopic partial resection with the unroofing technique (EPR-UT) 15. SLUB is a cap-based technique that involves suctioning the tissue into a cap and subsequently tightening a detachable loop to ligate the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…However, a meta-analysis that examined the diagnostic yield and complication rates of EUS-FNA, TCB, and EUS-FNB for patients with gastrointestinal stromal tumors (GIST) demonstrated no significant differences between the techniques 10. To improve diagnosis of SELs, several new tissue acquisition methods have been proposed, including suck-ligate-unroof-biopsy (SLUB) 11, use of endoscopic submucosal dissection (ESD) technique 12 13 14, endoscopic partial resection with unroofing technique (EPR-UT) 15, and single-incision needle-knife (SINK) biopsy 16. When performing SINK, the overlying mucosa of a SEL is opened with a single linear incision using a standard needle knife and tissue samples are obtained by passing conventional biopsy forceps through the opening and deep into the lesion.…”
Section: Introductionmentioning
confidence: 99%
“…However, it might be more difficult to obtain tissue from a lesion located in extraluminal regions. 29,[33][34][35] Recently, new endoscopic resection techniques, including laparoscopic endoscopic cooperative surgery, 36 endoscopic full-thickness resection, and endoscopic submucosal tunnel dissection were developed. These techniques are safe and effective for small GISTs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several diagnostic techniques, such as EUS‐guided fine‐needle aspiration (EUS‐FNA), EUS‐guided trucut biopsy (EUS‐TCB), and other biopsy techniques based on endoscopic mucosal resection or endoscopic submucosal dissection (ESD), have emerged as methods for samples of SELs to theoretically overcome the disadvantages of EUS . However, current studies demonstrated that EUS‐FNA had variable diagnostic yields of 38–82% because of inadequate tissue acquisition, whereas EUS‐TCB was limited by technical constraints such as angulation caused by the stiffness of the device .…”
Section: Introductionmentioning
confidence: 99%